Introduction to "Globalization and Its Discontents: Exposing the Underside". - Hu-Dehart, Evelyn (Frontiers: A Journal of Women Studies, 2023)
This article explores the negative effects of globalization, particularly on Third World women. It discusses the exploitation and abuses faced by these women as a result of late capitalist globalization and neoliberalism. The author emphasizes the intersectionality of race, class, gender, and nationality in understanding the impact of globalization. The article also examines the Zapatista uprising in Mexico and the role of maquiladoras in perpetuating inequality. It concludes by acknowledging the importance of grassroots perspectives and the need to learn from young Asian American and feminist scholars and activists. The text raises questions about fair wages, workplace standards, and human rights implications of globalization, and argues for a change in the man-made system.